Pemberdayaan UMKM Melalui Digitalisasi: Meningkatkan Daya Saing Produk Lokal di Desa Bowong Cindea Kabupaten Pangkep - Fatmawaty, A. St. Fatmawaty; Bijaksana, A. Muh. Arif Bijaksana; Buarlele, Luciana Buarlele; Khaeriyah, Khaeriyah (ADPERTISI, 2024)
Empowering Micro, Small and Medium Enterprises (MSMEs) through digitalization is astrategic step to improve the competitiveness of local products in Indonesia, especially in rural areas. This research aims to explore the application of digitalization in improving thecompetitiveness of local products in Bowong Cindea Village, Pangkep Regency. The method used in this research is a combination of qualitative and quantitative approaches, with data collection through in-depth interviews, participatory observation, surveys, and documentation studies. The research respondents consisted of MSME players in Bowong Cindea Village as well as other related parties, such as training institutions and village government. The results show that the use of ecommerce platforms and social media significantly increases market reach and sales of local products. However, challenges such as limited internet access, lack of digital understanding, and limited capital for technology investment are still obstacles. Nonetheless, digitalization is proven to have a positive impact in improving the competitiveness and productivity of MSMEs in these villages. This study provides recommendations for policy makers and related parties to strengthen digital infrastructure, provide ongoing training, and encourage MSME participation in digitalplatforms to expand the market for local products.